2008
DOI: 10.1089/ars.2007.1897
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation in the Pathogenesis of Idiopathic Pulmonary Fibrosis

Abstract: The role of inflammation in idiopathic pulmonary fibrosis (IPF) is controversial. If inflammation were critical to the disease process, lung pathology would demonstrate an influx of inflammatory cells, and that the disease would respond to immunosuppression. Neither is true. The classic pathology does not display substantial inflammation, and no modulation of the immune system is effective as treatment. Recent data suggest that the pathophysiology of the disease is more a product of fibroblast dysfunction than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
193
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(199 citation statements)
references
References 151 publications
3
193
0
3
Order By: Relevance
“…This finding further suggests that Doxy restores the balance of epithelial-mesenchymal cells by inhibiting the TGF-ÎČ signaling pathway and suppressing oxidative stress and inflammation to alleviate epithelial cell injury. Inflammation plays a role in disease genesis and progression in both human IPF and murine models of PF (30). In this study, we analyzed the effect of Doxy on inflammation by evaluating the levels of inflammatory cytokines in mouse plasma.…”
Section: Discussionmentioning
confidence: 99%
“…This finding further suggests that Doxy restores the balance of epithelial-mesenchymal cells by inhibiting the TGF-ÎČ signaling pathway and suppressing oxidative stress and inflammation to alleviate epithelial cell injury. Inflammation plays a role in disease genesis and progression in both human IPF and murine models of PF (30). In this study, we analyzed the effect of Doxy on inflammation by evaluating the levels of inflammatory cytokines in mouse plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanism of PF has not been fully revealed. But inflammation was thought as an important characteristic of pulmonary fibrosis and also a major reason of pulmonary fibroblast proliferation (Bringardner et al, 2008). Inflammation and the initial immune response induce secretion disorder of cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…idiopathic cases (Bringardner et al, 2008), and toll like receptor 4 (TLR4) play a critical role in inflammatory response. Recently, several researches suggested that TLR4 signaling pathway is involved in PFprocess.…”
Section: Introductionmentioning
confidence: 99%
“…Controversy regarding the role of inflammation in the pathogenesis of IPF persists, 42 with the prevailing hypothesis being that inflammation does not play a major role in the pathogenesis of IPF. [43][44][45] Our data are notable because they correlate the presence of mast cells, a specific type of inflammatory cell, with slower loss of lung function in IPF patients.…”
Section: Discussionmentioning
confidence: 99%